2020
DOI: 10.1002/ajhb.23496
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference percentiles for Hispanic‐American children and comparison with other international references

Abstract: Introduction Waist circumference (WC) constitutes an indirect measurement of central obesity in children and adolescents. Objective To provide percentiles of WC for Hispanic‐American children and adolescents, and compare them with other international references. Materials and methods The sample comprised 13 289 healthy children between 6 and 18 years coming from public schools of middle and low socioeconomic levels in different parts of Argentina, Cuba, Spain, Mexico, and Venezuela. The LMS method to calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…27,29 The WC p>90 is a good variable to estimate excess of android fat in Brazilian children between 8-9 years old, as demonstrated by Filgueiras et al 20 However, the cutoff to WC in children are influenced by sex and ethnicity. [29][30][31] As recently proposed by Santos et al, the WC p>75 can be considered a cutoff for the risk of obesity in Brazilian children aged 6-8 years 14 . In our study, the Spearman correlation demonstrated that WC p>80 was more strictly related to metabolic and pressure alterations than the Z score of BMI.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…27,29 The WC p>90 is a good variable to estimate excess of android fat in Brazilian children between 8-9 years old, as demonstrated by Filgueiras et al 20 However, the cutoff to WC in children are influenced by sex and ethnicity. [29][30][31] As recently proposed by Santos et al, the WC p>75 can be considered a cutoff for the risk of obesity in Brazilian children aged 6-8 years 14 . In our study, the Spearman correlation demonstrated that WC p>80 was more strictly related to metabolic and pressure alterations than the Z score of BMI.…”
Section: Discussionmentioning
confidence: 93%
“… 27 , 29 The WC p>90 is a good variable to estimate excess of android fat in Brazilian children between 8–9 years old, as demonstrated by Filgueiras et al 20 However, the cutoff to WC in children are influenced by sex and ethnicity. 29 , 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…There was no pubertal stage or maturation differentiation between the groups of children and adolescents The groups categorization by age were founded in evidence of different existing percentiles of anthropometric measurements by sex and age, as well as cut-off points to assess central obesity in children, adolescents, and adults. In fact, BMI and waist circumference show differences by age [27,28], tending to increase its values with age [29] and suggesting that mortality risk is also age related [30].…”
Section: Design and Participantsmentioning
confidence: 99%